The relationship of resilience and self-compassion of Malaysian tertiary students - Karnaen, Nurkhairiah; Abdul Latif @ Bapoo, Lilisuriani (IIUM Press, 2017)
Employability has always been a concerning issue involving tertiary level students in Malaysia. A lot of employers perceive Malaysian graduates as being unsuited for employment and resilience is considered a desired trait for employability. The research investigated the level of resilience and self-compassion among tertiary level students in Malaysia. The study aimed to find out the relationship between self- compassion and resilience as both concepts proved to share a similar result of minimizing negative effects. The Brief Resilience Scale and Self-Compassion Scale- Short Form was distributed to 171 students studying in tertiary level institutions all over Malaysia. Research result showed that the relationship between resilience and self-compassion is positive and significant. The level of resilience and self- compassion is at moderate level for the respondents. It is recommended for future similar study to be done on larger number of respondents.